"The screening of Indian Hindi films in Pakistan for the Survival of the Pakistani Film Industry" - Kashif, Raja (sourcecoder, 2024)
Feature films, a powerful medium of mass communication and a visual representation of literature, offer a captivating audio-visual experience. Modern technology enhances this experience, making films an integral part of contemporary life. As a rich medium for reflecting on human nature, films provide unique insights into diverse cultures, challenging stereotypes, and fostering understanding. This paper examines the socio-political phenomenon of Indian Hindi film screenings in Pakistan. Despite political divisions in the subcontinent, films serve as a valuable tool for studying and promoting soft social change. This analysis explores the complex interplay of political and social factors that influence the reception and impact of Indian Hindi films in Pakistan.